Fauna de abelhas nativas de duas áreas de restinga do Parque Estadual de Itaúnas, Espírito Santo, Brasil - Receputi, Ana Luiza Morati (2015)
Two studies were carried out in this dissertation: (i) the inventory of the native bee fauna (regarding species richness, diversity and composition) in forestal and herbaceous/shrubby restinga at the Parque Estadual de Itaúnas, Espírito Santo, Brasil, and (ii) the inventory of orchid-bee fauna (also comprising species richness, diversity and composition) in the same areas. Both studies aimed at answering two directly related questions: 1) Are the composition, richness and diversity of native bee and orchid-bee faunas in forest and herbaceous/shrubby restinga different? 2) Are these faunas more related, respectively, to forest formations or to open formations? Sampling was carried out monthly from November/2013 to August/2014, using traps to attract male orchid-bees and hand nets to collect bees in general on flowers. In both areas 2.448 individuals were sampled, belonging to 71 species. From these, 300 individuals belonging to 45 species were sampled in the forest resting, and 486 individuals belonging to 40 species were sampled in the herbaceous/shrubby resting, using hand nets. Regarding orchid-bees, 838 males belonging to 17 species were sampled in the forest resting, and 824 males belonging to 12 species were sampled in the herbaceous/shrubby restinga. Results suggest that in both cases, the species compositions of the two areas are different and richness and diversity were greater in forest restinga areas. As for the native bees fauna, considering species richness and composition, the faunas of the Parque Estadual de Itaúnas were more similar to open formation and/or modified areas and with severe characteristics. The orchid-bee faunas from both areas were characterized by the presence of species with high plasticity, related to their presence in locations with different vegetation structure, species that are apparently associated with open and/or edge environments and, in the forest restinga, the fauna was also characterized by the presence of species with greater association with forests and preserved environments. The original prediction that the restinga forest fauna would be more related to forest areas while that of the herbaceous/shrubby would be more related to those of open areas was not totally confirmed.